NON-PERFORMING PROPERTY LOANS AND ITS ORIGINATION IN THE REAL ESTATE FINANCE SYSTEM: CASE STUDY OF MALAYSIA - Kuen Wei, Tham; Said, Rosli (International Journal of Property Sciences (E-ISSN: 2229-8568), 2021)
A healthy real estate finance system is crucial for any economy to grow and thrive. However, in recent years, the sustainability and soundness of the Malaysian Real Estate Finance System had been in question as the number of non-performing property loans had been on the rise. This paper looks into how property NPLs originate within the real estate finance system in Malaysia and its current performance in Malaysia. A descriptive research design was conducted utilizing in-depth case studies of Malaysia to examine Malaysia’s real estate finance system consisting of loan originators in the primary market and the special purpose vehicle involved at the secondary mortgage market where it was found that the Malaysian Real Estate Finance System is efficiently developed and on par with other developed countries with a robust primary mortgage market, effective secondary mortgage market and a vibrant capital market. Further analysis found that there are a total of 57 financial institutions that are property loan originators in Malaysia that consists of 26 Commercial Banks, 16 Islamic Banks, 2 International Islamic Banks, 11 Investment Banks, and 2 Special Financial Institutions. In terms of NPLs in Malaysia, property loans are the largest component of total NPLs in the country, and subsequent analysis found that the number of property NPLs in the country had been rising since 2015, after a long decade decline. This study warrants further research into the causes of property NPLs in the country so that the causes of property NPLs can be monitored as part of the country’s strategic monetary policy to control and reduce the number of property NPLs in the country. Ultimately, this also helps to contribute towards a sound and robust real estate finance system in Malaysia.